The Study of Heart Rate Variability (HRV) Biofeedback Through Zikir (Islamic Recitation) of High School Students - Mohd Rozali, Senik; Muhammad Nubli, Abdul Wahab; Mardiyyah, Zamani (2013)
Zikir has been known to have a direct impact on the individual. Zikir is able to help individuals make behavioral changes. Zikir is known to have an impact on the mind, emotions and behavior. An investigation was conducted to identify the extent implemented zikir able to help individuals make changes themselves. Clinical studies carried out by taking 10 respondents among secondary school students who were involved in the disciplinary problems. Zikir intervention enables us to make changes ourselves using the technique of "Heart Rate Variability" (HRV). Students were given technical chanting slowly, loudly, and several techniques of zikir such as tahlil, istigfar and salawat. Conversion EmWave had recorded using a look at how the students were able to make changes themselves. The study found that students who successfully completed the zikir training able to make changes themselves. Students had successfully made a change to the change score "HRV Coherence" of the VLF spectrum of LF and HF spectrum conditions. This technique can be used in schools to improve the effectiveness of prevention of diciplinary problems therefore enabling education programs to be implemented.